Back Cover: Stabilization of Copper Catalysts for Liquid‐Phase Reactions by Atomic Layer Deposition (Angew. Chem. Int. Ed. 51/2013). Issue 51 (28th November 2013) - O'Neill, Brandon J.; Jackson, David H. K.; Crisci, Anthony J.; Farberow, Carrie A.; Shi, Fengyuan; Alba‐Rubio, Ana C.; Lu, Junling; Dietrich, Paul J.; Gu, Xiangkui; Marshall, Christopher L.; Stair, Peter C.; Elam, Jeffrey W.; et al.
<x xml:space="preserve">Abstract</x> Deactivation of heterogeneous catalysts is an important issue in liquid‐phase catalytic processes and for the utilization of base metal catalysts, such as copper. In their Communication on page 13808 ff., J. A. Dumesic et al. show that atomic layer deposition can be used to build a protective coating around metallic nanoparticles, thereby preventing irreversible catalyst deactivation during liquid‐phase catalytic processing.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>